Epigenetic age acceleration and rheumatoid arthritis: an NHANES-based analysis and survival prediction models - Yuhang Ou; Zhihao Wang; Yunbo Yuan; Yuze He; Wenhao Li; Hao Ren; Junhong Li; Siliang Chen; Yanhui Liu (Clinical Epigenetics)
Abstract Objective Epigenetic aging has been confirmed to be associated with the pathogenesis of rheumatoid arthritis (RA), however, its role in the prognosis of RA remains unclear. Methods In this cross-sectional and prospective study, Epigenetic age and acceleration in participants of the National Health and Nutrition Examination Survey (NHANES) were calculated with Horvath’s clock, Hannum’s clock, PhenoAge, GrimAge, and GrimAge version 2 (GrimAge2). The association of epigenetic age and epigenetic age acceleration with the prevalence and overall mortality risk in RA was assessed with prediction models constructed. Results Accelerated epigenetic aging increased the risk of overall mortality in RA with hazard ratio of 1.075 (95% CI 1.043–1.107, p < 0.0001) for GrimAge2 acceleration (GrimAge2Accel) and 1.064 (1.032–1.098, p < 0.0001) for GrimAge acceleration (GrimAgeAccel). The GrimAge2Accel-based models, adjusted for a set of covariates composed of independent risk factors, excelled in predicting the 10 year and 20 year survival with area under curve of 0.760 (95% CI 0.621–0.898) and 0.823 (0.697–0.949), respectively. Conclusion Epigenetic aging may play a harmfully promotive role in the onset and progression of RA, and the GrimAge2Accel-based prediction models could effectively predict the survival of RA patients. Further research is needed to elucidate the underlying mechanisms and to explore the potential clinical implications.